(untitled) (Baghdad Science Journal, 2021)
Cutaneous leishmaniasis is one of endemic diseases in Iraq. It is considered as widely health problem and is an uncontrolled disease. The aim of the study is to identify of Leishmania species that cause skin lesions among patients in Thi-Qar Province, South of Iraq, also to detect some virulence factors of L. tropica. This study includes three local locations, Al-Hussein Teaching, Suq Al-Shyokh General and Al-Shatrah General Hospitals in Province for the period from the beginning of December 2018 to the end of September 2019. The samples were collected from 80 patients suffering from cutaneous leishmaniasis, both genders, different ages, various residence places and single and multiple lesions. Nested-PCR technique was used to amplify kinetoplast minicircle fragments DNA (kDNA). Conventional-PCR was performed for determination of some virulence factors (LPG1, GP63, CPA and PPG1 genes). The electrophoresis findings of kDNA gene showed two species of the parasite found in the study area, 65 samples were positive for cutaneous leishmaniasis, L. tropica at 750bp and L. major at 560bp. Generally, L. tropica (57.5%) was the most common specie and L. major (23.75%) appeared in a low level. There are no significant differences between the infections of males and females, while there are significant differences at the comparison between age groups. All virulence genes (LPG1, GP63, CPA and PPG1) appeared in all L. tropica isolates with high percentage (100%). L. tropica is the major specie which that caused CL in Thi-Qar province, while L. major appeared in low incidence. The virulence genes, which were reviewed, are necessary and important in pathogenesis of L. tropica.